Mind Control Using Psycotronics (International Journal of Engineering and Computer Science, 2017)
This paper deals with the mind control using psychotronics as a directed energy weapons & its relevant uses in human life in present day. These device works on the principle of squad(ssss) or e.m wave. We are very thankful Prof. Sitanshu Ray for his tireless support and his lucid way of explaining us the salient points really helped us to write this paper.